Measurements of differential cross sections of top quark pair production as a function of kinematic event variables in proton-proton collisions at $ \sqrt{s}=13 $ TeV - CMS collaboration (2292 authors) (2018)
Measurements of differential $ t\overline{t} $ production cross sections are presented in the single-lepton decay channel, as a function of a number of kinematic event variables. The measurements are performed with proton-proton collision data at $ \sqrt{s}=13 $ TeV, collected by the CMS experiment at the LHC during 2016, with an integrated luminosity of 35.9 fb$^{−1}$. The data are compared to a variety of state-of-the-art leading-order and next-to-leading-order $ t\overline{t} $ simulations.